Stress in Pregnant Women during the COVID-19 Pandemic - Kostic, Konstantin; Kostic, Aleksandra; Banjanin, Nikolina; Milin-Lazovic, Jelena (Medical Research, 2024)
Introduction: Pregnancy is a vulnerable period in a woman’s life when psychological distress can have negative consequences for the mother and fetus. Pregnant women and women in labor are at increased risk of developing a more severe clinical picture of COVID-19 infection compared to non-pregnant women. Aim: Examination of stress in pregnant women in Serbia during the COVID-19 pandemic. Material and methods: Pregnant women were given an anonymous questionnaire during outpatient prenatal care. Socio-demographic characteristics, obstetric factors, COVID-19 history, DASS-21 questionnaire, and PREPS questionnaire were examined. Results: Within the PREPS questionnaire, the average score for the domain “preparedness for childbirth” is 2.4±0.9, for the domain “infection” 2.9±1.0, and for the domain “positive appraisal” 3.7±0.8. A positive, weak, statistically significant correlation was registered between the domains ‘’childbirth preparedness” and the domains “depression” and “anxiety” on the DASS-21 questionnaire. A positive, moderate, statistically significant correlation was registered between the domain “childbirth preparedness” and the domain “stress” on the DASS-21 questionnaire. A positive, weak, statistically significant correlation was registered between the domain “infection” and “stress” on the DASS-21 questionnaire. Conclusion: Two years after the pandemic was officially declared, pregnant women either had a previous COVID-19 infection or were vaccinated against it, so the scores of the domains "preparation for childbirth" and "infection" were lower than expected, while the score for the domain "positive appraisal" is higher compared with studies conducted at the beginning of the pandemic. The obtained results strengthen future research on the association of depression, stress, and anxiety with stress in pregnancy caused by the COVID-19 pandemic. Keywords: pregnancy, stress, COVID-19